2004
DOI: 10.1007/s00421-004-1272-5
|View full text |Cite
|
Sign up to set email alerts
|

Velocity at V?O2 max and peak treadmill velocity are not influenced within or across the phases of the menstrual cycle

Abstract: Velocity at VO(2 max) (vV(.)O(2 max)) and peak treadmill velocity (PTV) are variables highly predictive of endurance performance. However, how these variables are affected by the menstrual cycle is unknown. The aim of this study was to assess the effect of the menstrual cycle on vV(.)O(2 max) and PTV. Ten, female runners were studied across three menstrual cycles. Training, menstrual history and mood states were assessed for 2 months, with daily salivary samples taken to detect menstrual phases. During the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Compared to other reports the VO 2 max achieved by male wrestlers in the present study (mean 58.9, ranged from 47.5 to 67.2 ml/min/kg) was greater than reported by Gale et al [10] in the American Olympic team (mean 54.3 ml/min/kg). The present values of VO 2 max were similar to those demonstrated by Yoon [5] in Korean wrestlers (60.0 ml/min/kg).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Compared to other reports the VO 2 max achieved by male wrestlers in the present study (mean 58.9, ranged from 47.5 to 67.2 ml/min/kg) was greater than reported by Gale et al [10] in the American Olympic team (mean 54.3 ml/min/kg). The present values of VO 2 max were similar to those demonstrated by Yoon [5] in Korean wrestlers (60.0 ml/min/kg).…”
Section: Discussionsupporting
confidence: 90%
“…Women were tested with no respect to their menstrual cycle. Menstrual cycle phase was not controlled, given that previous research suggested that maximal VO 2 is not affected by menstrual cycle phase [5]. All athletes were familiarized with the testing equipment and procedures prior to the commencement of testing.…”
Section: Methodsmentioning
confidence: 99%
“…It shows the maximum possible oxygen that human body can intake in one minute, and it is closely related to body endurance and aerobic activity and depends on the performance of skeleton, muscular, and cardiovascular systems [4]. In addition, maximum anaerobic power (pmax) is the ability of all muscles to produce more force with high speed in sprint activities for a very short time [5].…”
Section: Introductionmentioning
confidence: 99%
“…No differences have been found in the aerobic performance (VO 2 max) during the phases of the menstrual cycle, regardless of whether or not the subject is taking oral contraceptives (Burrows & Bird, 2005;Lamina, Hanif, & Muhammed, 2011;Máček & Radvanský, 2011;Oosthuyse, Bosch, & Jackson, 2005;Vaiksaar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%